2009
DOI: 10.1126/science.1167337
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic Sleep Pressure and Responses to Sustained Attention in the Suprachiasmatic Area

Abstract: Throughout the day, cognitive performance is under the combined influence of circadian processes and homeostatic sleep pressure. Some people perform best in the morning, whereas others are more alert in the evening. These chronotypes provide a unique way to study the effects of sleep-wake regulation on the cerebral mechanisms supporting cognition. Using functional magnetic resonance imaging in extreme chronotypes, we found that maintaining attention in the evening was associated with higher activity in evening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
140
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 171 publications
(153 citation statements)
references
References 21 publications
10
140
1
1
Order By: Relevance
“…Through LC activity with its widespread tha lamic and cortical connections, this pathway may control a variety of central nervous system functions related to noradrenergic innervations, including alert ness and vigilance, and also higherorder cognitive processes. We have recently collected indirect evidence that the circadian arousal signal generated by this circuitry is modulated by homeostatic sleep pressure (Schmidt et al, 2009). In this study, the interaction between these processes at the cerebral level was investi gated in chronotypes differing in circadian and homeostatic sleep-wake regula tory processes under normally entrained day-night conditions (Baehr et al, 2000;Bailey and Heitkemper, 2001;Kerkhof, 1991;Kerkhof and Van Dongen, 1996;Mongrain et al, 2004Mongrain et al, , 2006aMongrain et al, , 2006b.…”
Section: Circadian and Homeostatic Impetus For Wakefulnessmentioning
confidence: 99%
“…Through LC activity with its widespread tha lamic and cortical connections, this pathway may control a variety of central nervous system functions related to noradrenergic innervations, including alert ness and vigilance, and also higherorder cognitive processes. We have recently collected indirect evidence that the circadian arousal signal generated by this circuitry is modulated by homeostatic sleep pressure (Schmidt et al, 2009). In this study, the interaction between these processes at the cerebral level was investi gated in chronotypes differing in circadian and homeostatic sleep-wake regula tory processes under normally entrained day-night conditions (Baehr et al, 2000;Bailey and Heitkemper, 2001;Kerkhof, 1991;Kerkhof and Van Dongen, 1996;Mongrain et al, 2004Mongrain et al, , 2006aMongrain et al, , 2006b.…”
Section: Circadian and Homeostatic Impetus For Wakefulnessmentioning
confidence: 99%
“…Moreover, a recent study incorporating behavioral assessments, EEG, and functional magnetic resonance imaging (fMRI) in morning and evening chronotypes indicated that homeostatic sleep pressure exerts an influence on attention-related cerebral activity in key structures crucially involved in generating the circadian wake-promoting signal, including the locus coeruleus. Specifically, maintenance of optimal attentional performance in the evening after a normal waking day was associated with higher activity in evening chronotypes than in morning chronotypes in locus coeruleus and anterior hypothalamus, including the SCN (Schmidt et al 2009). Furthermore, activity in the anterior hypothalamus decreased with increasing homeostatic sleep pressure, as indexed by EEG SWA in the first NREM sleep episode.…”
Section: Cerebral Underpinnings Of Circadian and Homeostatic Influencmentioning
confidence: 99%
“…We originally identified the localization of the blood oxygen level-dependent (BOLD) response using human brainstem atlases (3,4). Statistical inferences were based on a priori coordinates from previous independent publications reporting responses in the LC [see methods described in the Supporting Online Material for (2)]. The potential anatomical inaccuracy of these approaches led us to cautiously label the reported activation as LCcompatible, a localization disputed by Astafiev et al…”
mentioning
confidence: 99%
“…The warped T1 and mLC images averaged across subjects reflected group-wise variability in overall brain, brainstem, and LC anatomy, as observed in (2). Figure 1B (left panel) shows the location of the peak activation reported as "LC compatible" in Schmidt et al (1) on the mean T1 image, overlaid with the mean mLC image.…”
mentioning
confidence: 99%
See 1 more Smart Citation